Application of the Problem Based Learning (PBL) Model to Improve Chemistry Learning Outcomes in Class X of SMKN 2 Palembang - Ernita Putry Silaban; Muhammad Hadeli; Rahma Aini (Pedagogy Review, 2022)
Abstract: The Implementation of Problem Based Learning Model to Increase Student Learning Outcomes of Chemistry Subject in Tenth Grade of SMKN 2 Palembang. This Research aimed to determine the implementation of Problem Based Learning model to improve the student learning outcomes using Problem Based Learning (PBL) model. Research was done by two cycle and every cycle conducted two meetings with including planning stage, implementation, observation, and reflection. This research is conducted in SMKN 2 Palembang which the subject of research si students in X classs. The Populations is class X TKR 2, the subjects were 34 students. The instrument used observation sheet and the learning outcomes test. The result showed that of students learning outcomes is increased with the students average value of evaluation test for first cycle si 74 with the clasical percentage value is 70.59% and students average value of evaluation test for second cycle is 80 and the classical percentage value is 80. Depend on the result of the research showed that the implementation of Problem Based Learning model showed there is significant differences by using PBL. So, we can obtained that the teaching chemistry by using PBL is quite effective.Keywords: problem based learning, learning model, learning outcomes